2016
DOI: 10.1002/ceas.12042
|View full text |Cite
|
Sign up to set email alerts
|

In the Spirit of What Might Be Lost: Troubling the Boundaries of Good Fit

Abstract: Counselor Education and Supervision is a journal with the aim of enhancing the preparation of counselor educators, counselors, and supervisors. Editorial boards and editors may use the troubled concept known as good fit when considering manuscripts. Authors of potential manuscripts are encouraged to demonstrate scholarship, diversify author and participant type, and incorporate pedagogy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Even casual readers of the relevant counseling literature would have difficulty arguing with their central thesis, whether, "as a profession, we are asking the 'right' questions and studying the 'best' things to increase our collective understanding of the pedagogical foundations in counselor education" (p. 1). The authors echoed findings of two content analyses of teaching literature (Barrio Minton et al, 2018;Barrio Minton et al, 2014), the report of the Association for Counselor Education and Supervision (ACES) Teaching Initiative Taskforce (2016), and assertions of other counselor educators (e.g., Korcuska, 2016).…”
mentioning
confidence: 83%
“…Even casual readers of the relevant counseling literature would have difficulty arguing with their central thesis, whether, "as a profession, we are asking the 'right' questions and studying the 'best' things to increase our collective understanding of the pedagogical foundations in counselor education" (p. 1). The authors echoed findings of two content analyses of teaching literature (Barrio Minton et al, 2018;Barrio Minton et al, 2014), the report of the Association for Counselor Education and Supervision (ACES) Teaching Initiative Taskforce (2016), and assertions of other counselor educators (e.g., Korcuska, 2016).…”
mentioning
confidence: 83%
“…Recently, Barrio Minton et al (2018) found a sharp increase in empirical articles in counselor education articles between 2001-2010 and 2011-2015 incorporating pedagogical foundations, potentially due to the expansion of doctoral-level teaching and learning curricula and internships required by the 2016 Council for Accreditation of Counseling and Related Education Program (CACREP) Standards (2015). Korcuska (2016) cautioned that simply grounding the rationale for pedagogy studies in the CACREP standards could lead authors to overlook the underlying pedagogical structures and lead to studies without "heft or staying power" (p. 156). It is plausible to presume that it is uncertain if, as a profession, we are asking the "right" questions, and studying the "best" things to increase our collective understanding of the pedagogical foundations in counselor education.…”
mentioning
confidence: 99%
“…The first is foundational knowledge areas, which pertain to what graduate students aspiring to be counselors and counselor educators need to know to successfully engage in the profession. These knowledge areas have been addressed to some extent in the profession's literature and evolving accreditation standards (e.g., The Council for Accreditation of Counseling and Related Education Program [CACREP], 2015), but not recently within the context of a broad pedagogical structure (Korcuska, 2016). Second, Sexton suggested we learn more about how knowledge is most efficiently presented to students (and we would add how knowledge is evaluated).…”
mentioning
confidence: 99%